Rapid thermal annealing of Si paste film and pn-junction formation. (2nd July 2020) - Zhu, Huan; Sakamoto, Morihiro; Pan, Ting; Fujisaki, Takaya; Matsumoto, Hiroshige; Teii, Kungen; Kato, Yoshimine
Abstract: A Si nanoparticle paste has been studied to form a Si film on a substrate. Rapid thermal annealing (RTA) was conducted in order to recrystallize the Si paste which were prepared by a planetary ball milling grinding n-doped or p-doped Si chips. It was possible to minimize the oxidation during the melting process of Si nanoparticles with this RTA even at 1200 °C in 1 s. Lowering of the melting temperature appears to be due to the size effect and release of surface energy from the Si nanoparticles. RTA was conducted in an infrared furnace with temperatures varying from 1150 to 1300 °C. Si pn homo-junction structure was also fabricated by coating p-type followed by n-type Si pastes on a carbon substrate. Typical rectifying characteristics and slight photo-induced current was observed.